INVESTIGATION OF OVERPRESSURE AND MINERALOGY EFFECT ON ROCK MECHANICAL PROPERTIES OF MONTNEY SHALE GAS RESERVOIRS IN BRITISH COLUMBIA, CANADA - SAVITRI, CINDY DHEVAYANI (2021)
Numerous studies have been conducted to estimate dynamic rock mechanical properties (RMP) and rock strength of shale gas to predict accurate value when no core available. However, the existing correlations did not consider the overpressure condition and mineralogy in its correlations. These important parameters have to be considered to improve the accuracy of the correlations to optimized hydraulic fracturing design and operational strategy. The objective of this study is to improve the static and dynamic RMP correlations and develop a novel model of Unconfined Compressive Strength (UCS) by considering overpressure condition, mineralogy, and TOC content in Montney shale, British Columbia, Canada.